Leveraging the New Bottom-Up Economic Plan for Food System Transformation in Kenya: Podcast - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
The new Kenyan Government faces a complex domestic and global environment. It is expected to address these challenges with a new set of policies and programs as part of its most recent Bottom-Up Economic Plan, to which research-based evidence can contribute and support decision makers in the design and implementation process.